2013
DOI: 10.1111/ans.12330
|View full text |Cite
|
Sign up to set email alerts
|

Parapharyngeal pleomorphic adenoma as a cause of severe obstructive sleep apnoea

Abstract: A 26-year-old man presented with severe obstructive sleep apnoea that had progressively worsened over a 3-year period. His main complaints were heavy snoring, daytime somnolence, dysphagia and dysphonia. He reported no trismus, fever or other constitutional symptoms. Medical background included gastroesophageal reflux and smoking.Oral examination revealed a large, firm, non-tender swelling of the right peritonsillar/soft palatal region, causing deviation of the uvula to the contralateral side. On flexible naso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The majority of included patients had their neoplasms treated surgically, with 57 patients (72.2%) treated with surgery alone 9–12,14–61 . Two patients (2.5%) were treated with both surgery and radiotherapy, 13,62 and one patient (1.3%) treated with each of surgery and chemotherapy 63 and surgery and chemoradiotherapy 64 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of included patients had their neoplasms treated surgically, with 57 patients (72.2%) treated with surgery alone 9–12,14–61 . Two patients (2.5%) were treated with both surgery and radiotherapy, 13,62 and one patient (1.3%) treated with each of surgery and chemotherapy 63 and surgery and chemoradiotherapy 64 .…”
Section: Resultsmentioning
confidence: 99%
“…The location and size of the defect in the airway, and the nature of the underlying pathology may result in different responses to the effects of treatment on sleep disturbance. The obstructive effects of benign tumors in the oropharyngeal passage have been previously reported to be associated with sleep dysfunction, and effectively treated with surgery [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed no anemia, normal white blood count, isolated creatinine kinase elevation with normal myoglobin, normal renal function tests, slight elevation of the case series published report first symptoms to be an intraoral or cervical mass and cranial nerve neuropathy as the lesions may compress cranial nerves IX to XII 2,3,5 . Unusual presentations have been reported such as sleep obstructive apnoea 6 . What makes this case unique is the absence of any of the usual clinical signs.…”
Section: Case Presentationmentioning
confidence: 99%